2019
DOI: 10.1002/lary.27900
|View full text |Cite
|
Sign up to set email alerts
|

Arytenoid vertical height discrepancy in predicting outcomes after unilateral vocal cord medialization

Abstract: Objectives/Hypothesis Unilateral vocal fold paralysis is a structural abnormality that often occurs secondary to dysfunction of the recurrent laryngeal nerve and typically presents as a breathy voice. Medialization laryngoplasty is a constellation of procedures that improves apposition of the vocal cords. Many patients, however, fail to experience sufficient improvement in vocal quality postoperatively despite apparent glottic closure on stroboscopy. This suggests that asymmetry in other cord characteristics m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…8 Identification of a level difference between the two vocal folds is subjective and is also affected by perceptual differences in images obtained during a bird's eye view of the larynx during fibre-optic laryngoscopy. 11 This may explain the low incidence of this finding among those who required arytenoid adduction and also the presence of this finding among those who did not require arytenoid adduction in our study. In the latter scenario, it has also been suggested that absolute perfect approximation with respect to the vertical plane may not be essential for normal voice production and that the opposite cord may compensate to some degree for vertical misalignment.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…8 Identification of a level difference between the two vocal folds is subjective and is also affected by perceptual differences in images obtained during a bird's eye view of the larynx during fibre-optic laryngoscopy. 11 This may explain the low incidence of this finding among those who required arytenoid adduction and also the presence of this finding among those who did not require arytenoid adduction in our study. In the latter scenario, it has also been suggested that absolute perfect approximation with respect to the vertical plane may not be essential for normal voice production and that the opposite cord may compensate to some degree for vertical misalignment.…”
Section: Discussionmentioning
confidence: 47%
“…10 Medialisation thyroplasty with Silastic ® , which principally improves glottic closure by altering the membranous glottis, is currently the commonest surgical modality available for patients with unilateral vocal fold paralysis. 11 However, this procedure plays no role in repositioning the malpositioned arytenoid to its normal physiological position, which is a basic requisite for normal voice production. This was cited as the primary cause for this procedure yielding an unsatisfactory result in numerous cases, when performed alone.…”
Section: Discussionmentioning
confidence: 99%
“…The closure of the anterior commissure can be relatively easily restored by a variety of injected materials or implants 9 . However, considering the complex movement of the arytenoid cartilage, 46–49 restoring optimal closure of the respiratory glottis in patients with UVFP is a more complicated issue. The exact anatomy and kinesiology of the cricoarytenoid joint is still a matter of debate today 46,50–53 .…”
Section: Discussionmentioning
confidence: 99%
“…The VHI‐10 is a scale which was designed to evaluate the impact of voice disorders on patients' quality of life by providing a subjective self‐assessment of voice 6 . The scale quantifies a patient's own perception of handicap, disability and distress attributed by his/her voice 7 . The validation studies of the VHI‐10, including the initial proof of concept and subsequent assessments of its Minimal Clinical Important Difference (MCID), were conducted based on surveys collected in the otolaryngologists’ office 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…6 The scale quantifies a patient's own perception of handicap, disability and distress attributed by his/her voice. 7 The validation studies of the VHI-10, including the initial proof of concept and subsequent assessments of its Minimal Clinical Important Difference (MCID), were conducted based on surveys collected in the otolaryngologists' office. 8,9 In considering the clinical applicability of PROMs, it is important to ensure that the PROM is both validated and correctly measures its intended outcome.…”
Section: Introductionmentioning
confidence: 99%